Species composition and abundance of weeds in tomato fields with nematicidal potential against Meloidogyne incognita - MUH. ADIWENA; ADITYA MURTILAKSONO; ANKARDIANSYAH PANDU PRADANA; AISYAH RIZKY PARAMESWARI; DIANA PUTRI (Society for Indonesian Biodiversity, 2025)
Abstract. Adiwena M, Murtilaksono A, Pradana AP, Parameswari AR, Putri D. 2025. Species composition and abundance of weeds in tomato fields with nematicidal potential against Meloidogyne incognita. Biodiversitas 26: 5891-5905. Root-knot nematodes (Meloidogyne incognita) cause major crop losses worldwide, yet sustainable management options remain limited. This study assessed weed community structure in tomato fields and tested the nematicidal activity of dominant species. Quadrat sampling (1×1 m) recorded seven species from six families, with moderate diversity (Shannon-Wiener H?: 1.125), low evenness (E: 0.578), and high dominance (Simpson’s D: 0.470). Alternanthera philoxeroides was ecologically dominant (IVI: 72.0%; RD: 62.5%), while Eleusine indica and Cyperus rotundus were most frequent (RF: 23.8%). Aqueous root extracts (20% w/v) were tested in vitro, and proportion data were arcsine square-roots transformed and analyzed using one-way ANOVA followed by Tukey’s HSD test (?: 0.05). A. philoxeroides achieved the strongest egg-hatch inhibition (98.2±0.45% unhatched eggs at 168 h vs. 69.6±3.58% in control), while Cleome rutidosperma induced the highest J2 mortality (21.8±6.14%). Gas chromatography-mass spectrometry (GC-MS) revealed 12 constituents in A. philoxeroides and 18 in C. rutidosperma. Key compounds included methyl palmitate, methyl oleate, and methyl linoleate in A. philoxeroides; and lauric acid, methyl palmitate, and 9,12-octadecadien-1-ol in C. rutidosperma. These phytochemicals are consistent with the observed suppression of egg hatching and juvenile survival. To our knowledge, this is the first study in Indonesia to explicitly link weed community diversity with in vitro nematicidal activity against M. incognita in tomato fields. By integrating ecological survey and bioassay data, this work demonstrates that naturally occurring weeds can serve both as indicators of agroecosystem health and as practical, locally available sources of botanical nematicides. The findings emphasize two major contributions: first, to nematode management through eco-friendly suppression of root-knot nematodes; and second, to biodiversity conservation by recognizing weeds as functional components of sustainable agroecosystems.